Brachypodium distachyon as alternative model host system for the ergot fungus Claviceps purpurea. (5th June 2017) - Kind, Sabine; Schurack, Selma; Hinsch, Janine; Tudzynski, Paul
Summary: To investigate its susceptibility to ergot infection, we inoculated Brachypodium distachyon with Claviceps purpurea and compared the infection symptoms with those on rye ( Secale cereale ). We showed that, after inoculation of Brachypodium with Claviceps, the same disease symptoms occurred in comparable temporal and spatial patterns to those on rye. The infection rate of Claviceps on this host was reduced compared with rye, but the disease could be surveyed by fungal genomic DNA quantification. Mutants of Claviceps which were virulence attenuated on rye were also affected on Brachypodium . We were able to show that pathogenesis‐related gene expression changed in a typical manner for biotrophic pathogen attack. Our results indicated that the Claviceps – Brachypodium interaction was dependent on salicylic acid, cytokinin and auxin. We consider Brachypodium to be a suitable and useful alternative host; the increased sensitivity compared with rye will be valuable for the identification of infection mechanisms. Future progess in understanding the Claviceps –plant interaction will be facilitated by the use of a well‐characterized model host system.